PENGARUH POLA TANAM TERHADAP PERTUMBUHAN TANAMAN REHABILITASI HUTAN DAN LAHAN DI RPH TAROGONG BKPH LELES KPH GARUT - Raizal Fahmi Solihat; Yaya Sunarya (Wanamukti: Jurnal Penelitian Kehutanan, 2021)
ABSTRACTThis study aims to determine whether there is an effect of cropping plants on the growth of pine (pinus merkusii), eucalyptus (eucaliptus alba), puspa (schima wallichii) and avocado species (parsea americana) on RHL activities in RPH Tarogong, BKPH Leles, KPH Garut, West Java and Banten regional divisions. This study was conduct in three series. First, determining the location to be measure second, determination of the measuring plot. Third, making plant measuring by size 40x25m with an area 0,1ha by using systematic sampling with random start metode. Primary data retrieval, namely from the results of the making of the measuring plots according to the plan, then recorded in the taly sheet and then processed according to the parameters determined in the study. Data analysis was conduct to determine the role of each cropping pattern on diameter. The height and robustness of the plants were analyze using the independent sample t-test of the unpaired independent variables. Thus, we can formulate a general definition that the independent sample t is a statistical analysis that aims to compare two unpaired samples. Based on the results of study and discussion, it can be concluded that the growth of eucalyptus (Eucaliptus Alba) and Puspa plant spesies (Schima Wallichii) is better in the agroforestry pattern than in the non-agroforestry pattern. The growth of pine (Pinus Merkusii) and avocado plants (Parsea Americana) is not affect by cropping patterns, so these types can be plant in both agroforestry and non-agroforestry cropping patterns.